Música como aia da vontade: ensaio sobre a leitura wagneriana de Schopenhauer - Barros, Márcio Benchimol [UNESP] (Universidade Federal de Minas Gerais (UFMG), Dept. Filosofia, 2012)
In the year 1851, Richard Wagner had his first contact with the philosophy of Schopenhauer, a fact that was followed soon by his proclaimed and somewhat surprising conversion to schopenhauerianism. Tweny years later, his debt to Schopenhauer is reaffirmed in Beethoven, a comemorative writing in which are to be found the outlines of a philosophy of music - claimed by the composer to be based on Schopenhauer's aesthetics - that had great influence in Nietzsche's theoretical elaboration of the dionysiac, as it appears in The birth of Tragedy. My work aims primarily at investigating to what extent the musical aesthetics outlined in Beethoven is actually compatible with that presented in The world as Will and representation. The pointing out of remarkable differences between the two aesthetic conceptions gives then rise to some reflexions concerning the character of the relations between Wagner, Schopenhauer and the young Nietzsche.
Music as a lady of will essay on the wagnerian reading of Schopenhauer
Keywords: Aesthetics; Music; Nietzsche; Schopenhauer; Wagner